The Impacts of Striped Snakehead (Channa striata Bloch) Fish Farming in Net Cages on Social, Economic and Environmental aspects in Bangkau Village, Hulu Sungai Selatan - Darda, Khalid; Mahyudin, Idiannor; Mahreda, Emmy Sri; Fitriliyani, Indira (International Journal of Environment, Agriculture and Biotechnology, 2019)
The purpose of this study was to analysis and identify the impacts of striped snakehead (Channa striata Bloch) fish farming in net cages on socio economic and environmental aspects. This study was a survey research. Location determination in Bangkau Village, Hulu Sungai Selatan Regency, South Kalimantan Province, Indonesia was done purposively because this area was a center for cultivating striped snakeheads in Hulu Sungai Selatan Regency. The collection of respondent data in this village was carried out in a census of 20 people from the whole population of cultivated striped snakeheads in net cages. The effect on social was done by identifying the effect of social aspect, the economic aspect determined by analysis used was the calculation of profit (π) and payback period (PP), while the environmental aspects, it was done by identifying the measurement of water quality. The results showed that from the social aspect, this business influenced the use of labor in its business, benefits obtained from the business of cultivating this striped snakeheads varied between 627,433.33 IDR to 9,789,533.33 IDR per year, while the payback period was 2.23 years. This cultivation effort from the environmental aspects of water quality is still within the class 3 water quality classification tolerance limit.